Chinese Cultural Acculturation as an Ethnosocial Learning Resource in Elementary Education - Pancasari, Devi; Ulfah, Fitriyah; Lestari, Purwaningrum Puji (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Background: The interaction between Chinese culture and local culture produces a unique cultural synergy, which broadens students' understanding of diversity. Learning rooted in local culture also strengthens the values of tolerance and the formation of multicultural identities among elementary school students.Purpose: This study aims to examine the acculturation of Chinese culture as an alternative to Natural and Social Sciences learning at SD Kalianyar I, Bangil.Method: Using a qualitative approach with ethnographic methods, this study presents the real form of acculturation results in physical forms such as architecture, household furniture, and culinary, as well as non-physical elements such as language, customs, and art performances. The sample consisted of 36 fifth-grade students enrolled in science and social studies. Data processing used NVivo 15.Result: The research findings show that students can identify, understand, and appreciate cultural heritage in their environment through contextual and exploratory learning activities.Theoretical implication: In the context of Natural and Social Sciences learning, Chinese cultural acculturation can be raised as learning material in both tangible and intangible forms.Practical implication: The existence of Chinese culture around the school plays an important role as a learning medium that supports the instillation of diversity values and the enrichment of Natural and Social Sciences material.